2017
DOI: 10.3390/ijerph15010031
|View full text |Cite
|
Sign up to set email alerts
|

Contact to Nature Benefits Health: Mixed Effectiveness of Different Mechanisms

Abstract: How can urban nature contribute to the reduction of chronic stress? We twice measured the concentration of the “stress hormone” cortisol in the hair of 85 volunteer gardeners (six months apart), relating cortisol level change to (self-reported) characteristics of their recreational activities. Both time spent in nature and physical activity led to decreases in cortisol, while time spent being idle led to an increase. At high levels of present stressors, however, the relationship for time spent in nature and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 55 publications
0
29
0
3
Order By: Relevance
“…The most common activity was walking and/or sitting (22). A few studies involved other activities such as gardening [30,37,54] and relaxation exercises in nature [53,54,59,60]. The durations of the interventions differed substantially and were spread between 15 and 55 min (14), one to several hours (3), one to several days (8), one to several weeks (3), and months (8) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common activity was walking and/or sitting (22). A few studies involved other activities such as gardening [30,37,54] and relaxation exercises in nature [53,54,59,60]. The durations of the interventions differed substantially and were spread between 15 and 55 min (14), one to several hours (3), one to several days (8), one to several weeks (3), and months (8) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies were CCTs. Two pre-post studies without control groups found no significant decrease from before to after the intervention [53,54]. There was an effect of condition (nature ˃ control) in the CCT study that included a stress recovery measure [46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive role of urban gardening in human well-being has also been explored [11]. Additionally, urban gardening has been proven to positively influence stress reduction outcomes [12], foster social cohesion while providing participants the opportunity to build social networks and connect to their community [13].…”
Section: Introductionmentioning
confidence: 99%